Knowledge of midwives about hypertensive disorders during pregnancy in primary healthcare - Ethelwynn L. Stellenberg; Nompumelelo L. Ngwekazi (AOSIS, 2016)
Background: Many factors or medical conditions may influence the outcome of pregnancy,which in turn, may increase infant and maternal morbidity and mortality. One such condition is an increase in blood pressure (BP). Setting: The study was conducted in maternity obstetrical units (MOUs) in primary healthcare clinics (PHCs) in the Eastern Cape, South Africa. Objectives: To determine the knowledge about hypertensive disorders during pregnancy (HDPs) of registered midwives working in MOUs in PHCs. Methods: A quantitative descriptive correlation research design was applied. A simple random sample of 43 (44%) rural and urban clinics was selected, and all registered midwives (n = 101) working in these clinics completed a self-administered questionnaire. Data were collected over a period of 1 month. The reliability and validity of the methodology were supported by experts and a pilot study. Descriptive statistics including various statistical tests to determine any associations between variables using a 95% confidence interval were applied. Results: A gap in the knowledge of midwives about HDPs was identified. Only 56.4% of the participants correctly answered the questions on the clinical manifestations of severe pre-eclampsia and 68.3% on the factors affecting BP, whereas 27.7% had no understanding about pre-eclampsia. Significant statistical differences were identified in the knowledge of staff in clinics where doctors visit regularly versus those in clinics where there are no visits (p = 0.04), and between experience of midwives and management of HDPs (p = 0.02). Conclusion: The knowledge of midwives is deficient regarding HDPs. Continuous professional development is critical in midwifery both in theory and in clinical practice. Keywords: Midwives; Hypertension; Eclampsia; Pre-eclampsia; Pregnancy